Judicial Assessment of Breach in Financing Agreements under Indonesian Contract Law - Rusli, Sandra; Djajaputra, Gunawan (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study examines legal protection in investment financing defaults through the South Jakarta District Court Decision No. 1216/Pdt.G/2024/PN Jkt.Sel. The dispute arose when the debtor, CV Niaga Traktor Utama, failed to fulfill installment obligations to PT Woori Finance Indonesia Tbk. Using a normative legal method with qualitative analysis, this research reviews primary and secondary legal sources. The findings show that creditor protection operates preventively through prudential assessment, collateral binding, and protective contractual clauses, and repressively through default claims and collateral execution. The debtor’s liability is grounded in fault-based responsibility, requiring compensation, surrender of collateral, and payment of litigation costs when obligations are unmet without justification. The decision reinforces pacta sunt servanda by upholding creditor rights while ensuring fairness and proportionality.